2002
DOI: 10.1097/00003246-200211000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an education program aimed at reducing the occurrence of ventilator-associated pneumonia*

Abstract: A focused education intervention can dramatically decrease the incidence of ventilator-associated pneumonia. Education programs should be more widely employed for infection control in the intensive care unit setting and can lead to substantial decreases in cost and patient morbidity attributed to hospital-acquired infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
3
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(163 citation statements)
references
References 30 publications
4
143
3
11
Order By: Relevance
“…We recommend that the clinician's practice include noninvasive mechanical ventilation over intubation when appropriate, oral intubation when an endotracheal tube is necessary, orogastric over nasogastric tubes, elevation of the head to at least 30°, minimization of sedation, administration of a proton pump inhibitor when prophylaxis is indicated, a frequency of ventilator tubing changes at 7 days or when soiled, avoidance or elimination of endotracheal tube leak, good technique in removal of condensate, and of course excellent hand hygiene. At this time we do not support the routine use of endotracheal tubes with subglottic suction capabilities, rota- (218). Success is dependent upon persistent attention to detail, high compliance rates, and a champion.…”
Section: Preventing Multidrug Resistancementioning
confidence: 84%
“…We recommend that the clinician's practice include noninvasive mechanical ventilation over intubation when appropriate, oral intubation when an endotracheal tube is necessary, orogastric over nasogastric tubes, elevation of the head to at least 30°, minimization of sedation, administration of a proton pump inhibitor when prophylaxis is indicated, a frequency of ventilator tubing changes at 7 days or when soiled, avoidance or elimination of endotracheal tube leak, good technique in removal of condensate, and of course excellent hand hygiene. At this time we do not support the routine use of endotracheal tubes with subglottic suction capabilities, rota- (218). Success is dependent upon persistent attention to detail, high compliance rates, and a champion.…”
Section: Preventing Multidrug Resistancementioning
confidence: 84%
“…The costs of these educational interventions are small in comparison with the estimated savings [17][18][19]36]. In these times of constrained financial resources, infection prevention and control measures become even more critical given the association between inadequate staffing in the ICU setting and increased rates of HCAI [36,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies over the last 10 years have demonstrated success in educating nursing staff [14,15] , critical care healthcare workers [16][17][18] as well as medical students and junior doctors [19] in the infection prevention and control of infection. The success of these numerous programmes is striking compared to the paucity of such interventions in the surgical arena.…”
Section: Education Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eğitim programlarının VİP'in önlenmesi konusunda oldukça yararlı olduğu göste-rilmiştir (24). Hemşirelik bakımı için özel protokoller hazırlanmasının da önlemede etkili olduğu saptanmış-tır (25).…”
Section: Mini Bronkoalveolar Lavaj (Bal)unclassified